PENERAPAN GOOD SCHOOL GOVERNANCE DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Bahrami, Maray Zahra; Ariani, Nita Erika; Fitri, Yulia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This study aims to determine the implementation of Good School Governance and the factors influencing it in junior high schools in Banda Aceh City. The sampling technique used was saturated sampling, in which there were 120 respondents from 30 public and private junior high schools in Banda Aceh City consisting of school principals, treasurers, administrative staff, and teachers. Data collection was carried out using a questionnaire which was distributed directly to respondents. The analytical method used was multiple linear regression with the SPSS version 29 application. The results showed that junior high schools in Banda Aceh City had implemented Good School Governance and Control Systems. Internal, Human Resource Competence and Utilization of Information Technology affect the variable Good School Governance. This means that the better the Internal Control System, Human Resource Competency, and Use of Information Technology, the better the implementation of good school governance. The use of Information Technology is the factor that has the greatest influence on Good School Governance. Utilization of Information Technology is the factor that has the greatest influence on Good School Governance. Suggestions for future researchers are to develop the research model used in this research, either by increasing the number of samples, replacing respondents with school committee members or other relevant school residents, and expanding the independent variables to be studied.